2020
DOI: 10.1111/pde.14339
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitor–induced hair loss in two adolescents

Abstract: A 14-year-old boy with a strong paternal history of male pattern hair loss showed no evident hair loss on physical examination on January 28, 2019 (Figure 1A). He began treatment with anastrozole in May 2019 for idiopathic short stature. Ten months after initiation of treatment, on February 3, 2020, he developed trichoscopy-confirmed androgenetic alopecia (AGA) with a female Ludwig II pattern, primarily involving the top of the scalp (Figures 1B and 2). The patient was subsequently treated with topical minoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…23 In a major meta-analysis, only seven articles were found that discussed AGA in patients under the age of 18, and six of these were retrospective reviews or case series/reports, which described a total of 124 patients (81 male). 24 Another review included information on 531 additional pediatric patients with AGA from three unpublished studies presented as conference abstracts in a single center. 18 Limitations of the study included the narrow group of subjects and limitation of the sample to a single city.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In a major meta-analysis, only seven articles were found that discussed AGA in patients under the age of 18, and six of these were retrospective reviews or case series/reports, which described a total of 124 patients (81 male). 24 Another review included information on 531 additional pediatric patients with AGA from three unpublished studies presented as conference abstracts in a single center. 18 Limitations of the study included the narrow group of subjects and limitation of the sample to a single city.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitations of the published studies, it is difficult to accurately assess the prevalence or incidence of AGA in the pediatric population 23 . In a major meta‐analysis, only seven articles were found that discussed AGA in patients under the age of 18, and six of these were retrospective reviews or case series/reports, which described a total of 124 patients (81 male) 24 . Another review included information on 531 additional pediatric patients with AGA from three unpublished studies presented as conference abstracts in a single center 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The remaining two patients were treated for hypertension. The comorbidities in this group include two patients with eczema, one patient with Klinefelter syndrome, one patient with idiopathic short stature, and two patients with refractory hypertension secondary to underlying renal disease [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Low-dose (≤ 25 Mg)mentioning
confidence: 99%
“…Of the 373 patients, the hair disorders treated include loose anagen syndrome, androgenetic alopecia (AGA), alopecia areata, telogen effluvium, short anagen syndrome, trichotillomania, wooly hair hypotrichosis, diffuse congenital hereditary generalized hypotrichosis, kerion alopecia, premature graying, and hypotrichosis simplex-corneodesmosin (CDSN) deficiency [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The majority of patients utilizing LDOM for hair noted improvement in hair density and a decrease in shedding [6][7][8][9][10][11][12][13][14][15][16]19].…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation